Cross-cultural adjustment of mainland chinese academic staff in Singapore. - Koh, Siew Cheng. (2008)
There has been much attention paid by scholars to the topic of expatriates' cross-cultural adjustment. Black, Mendenhall and Oddou [1991] have actually integrated past empirical studies to come out with a comprehensive model of international adjustment. Unfortunately, there has been few studies done on cultural adjustment of academic staff. This study examines the various factors that have an impact on Mainland Chinese academic staff in Singapore based on the data collected from Mainland Chinese academic staff in NTU, Jurong Campus.